New spaces for an ancient voice: can Arbëresh culture and its literary heritage thrive in the digital age? - Lila, Jolanda (Optime, 2025)
This article discusses attempts to safeguard the Arbëresh language and literature as an exception - al case of linguistic-ethnical vitality over time. The Arbëresh, the descendants of Albanian refu - gees who settled in Southern Italy from the 15th to 18th centuries, have preserved their language and some traditions as well as the Byzantine Rite while integrating deeply into Italian society. In the last decades, this heritage has faced challenges: globalization and technological change have eroded intergenerational transmission so much that UNESCO categored Arbëresh in 2010 as a “severely endangered” language. In response to these challenges, the study explores the transition of Arbëresh language and literature from traditional oral and written forms into the digital sphere. It argues that digitalization should not be seen merely as a technical process of preservation but as a strategic tool for addressing the con - temporary difficulties faced by minority cultures. By reflecting on the historical pillars of Arbëresh continuity—such as the gjitonia, the family unit, and religious institutions—the paper outlines a framework for digital revitalization, including the creation of digital corpora, the documentation of oral heritage, and the development of interactive learning platforms. The study concludes that strategically integrating digital tools can help overcome geographical dis - persion, reconnect the diaspora with its cultural roots, and support the long-term vitality of the Ar - bëresh language in the twenty-first century.